Estudio de factibilidad para la migración del sistema de ventas de la empresa Heli Market hacia cloud computing - Pazmiño Lema, Luis Alexander (2021)
This is a case study document, prior to the degree of systems engineer, this is oriented to the migration of systems to the cloud and its benefits, since at present, management software is a very necessary tool in all organizations and it is almost impossible to observe any consolidated company without having an information system or the slightest utilitarian application. As it refers to an information system operating in Heli Market, this case study is covered under the research sub-line of the systems engineering career, since the research line referred to is the following: "Communication and business and technological undertakings, development of information systems and the sub-line is data and telecommunications processes ”. In the same way, it was necessary to reinforce many important issues that may escape the author, as he did not yet have enough experience and in this case study, the technical participation of renowned engineering specialists in nearby city systems was invited, that they provided their contributions with references and knowledge so that this work has the proper computer technical guarantees referenced by highly experienced personnel who are currently practicing the profession; It is worth mentioning that this was also analyzed in depth by the author, who also provided a theoretical orientation, enriching this work with referenced theories, which have also allowed this present degree work to incorporate bibliographic citations of recognized authors at the level. world. In this document, annexes are also included, where the various evidences of participation in the interviews are detailed.